Constitutional and criminal bases for the criminalization of parental interference in Perú - Chavez Rojas, Sadi Antonio (2025)
Among the most critical problems in the family sphere, parental interference has generated serious consequences for society, parents, and especially for the child. The objective of this study is to determine how constitutional and criminal bases support the criminalization of parental interference in Peruvian law. A documentary approach based on legal dogmatics was used to analyze the relevant positive law. The results show that there are constitutional and legal foundations, both nationally and comparatively, that justify the criminalization of these actions. The conclusions confirm that parental interference involves actions by one parent to obstruct the relationship between the child and the other parent, which has led to the adoption of severe punitive sanctions in various international legislations